Long‐term results of the AIEOP LNH‐97 protocol for childhood lymphoblastic lymphoma. Issue 8 (8th March 2015) - Pillon, Marta; Aricò, Maurizio; Mussolin, Lara; Carraro, Elisa; Conter, Valentino; Sala, Alessandra; Buffardi, Salvatore; Garaventa, Alberto; D'Angelo, Paolo; Lo Nigro, Luca; Santoro, Nicola; Piglione, Matilde; et al.
ABSTRACT: Background: Treatment intensification was considered a suitable strategy to increase the cure rate of lymphoblastic lymphoma (LBL) in children. Procedure: The AIEOP LNH‐97 trial was run between 1997 and 2007 for newly diagnosed LBL in patients aged less than 18 years. Treatment schedule was based on the previous, LSA2‐L2 derived, AIEOP LNH‐92 protocol. Modifications included: increased dose of upfront cyclophosphamide and methotrexate, use ofl ‐Asparaginase during induction therapy, intensive block therapy for slow responders, and late intensification ("Reinduction") for patients with advanced stage disease. Total therapy duration was 12 months for stage I and II, and 24 months for stage III and IV. Central nervous system prophylaxis did not include cranial irradiation. Results: 114 eligible patients were enrolled, 84 males and 30 females; median age was 9 years. Complete remission was obtained in 98% of patients. After a median follow‐up time of seven years, 29 patients failed due to progression of disease (n = 2), relapse (n = 25), or second malignancy (n = 2). The 7‐year overall survival was 82% (standard error [SE] 4%) and the 7‐year event‐free survival was 74% (SE 4%). No subgroup showed significantly different event free survival. None of the patients died of front line chemotherapy‐related toxicity. Conclusions: Treatment intensification was associated with good outcome in children and adolescents with LBL, with limited toxicity. Prognosis after relapse was better for patients who underwent allogeneic hematopoietic stem cell transplantation. Measurements of biological markers and treatment response are necessary for achieving further improvement through more accurate identification and stratification of patients at risk of disease relapse. Pediatr Blood Cancer 2015;62:1388–1394. © 2015 Wiley Periodicals, Inc.